Decision Making of Full Speed, Slow Steaming, Extra Slow Steaming and Super Slow Steaming using TOPSIS - R.O. Saut Gurning; Wolfgang Busse; Mizan Lubnan (International Journal of Marine Engineering Innovation and Research, 2017)
Many shipping companies were trying to deliver their cargoes as quickly and reliably as possible. But in the beginning of the latest economic crisis on 2007, the containership fleet is slowing down. Even though world oil prices are now declining, but based on the prediction of World Bank, the price of oil will rise again in 2017. Even some shipping company implements slow steaming method on the operation of their ships. But they do not know whether these methods are effective or not due to any negative effects arising from an implement of slow steaming like increased sailing time so may result in losses to the shippers. This study aims to give suggestions on which ship speed is most optimal for shipping companies by considering technical and operational, financial and also environmental aspect then will be selected one by using Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. While for criteria and sub criteria weighting are calculated by Analytic Hierarchy Process (AHP) method using Expert Choice software. From the TOPSIS method, super slow steaming was chosen to be the first rank.